Short communication: U.S. dairy selection programs impact in Argentina - Marini, P. R.; López, R. G.; Di Masso, R. J. (Cuban Journal of Agricultural Science, 2016)
The aim of this study was to evaluate the milk index as an indicator of productive efficiency for dairy cows on pasture systems, compared with the usual indicator based solely on accumulated individual production. Age, total milk production and milk index from 127 dairy cows, classified by the Holstein Argentino Breeders Association (ACHA), were used, showing a cumulative production greater than 50,000 liters. Data were obtained from a commercial herd kept in the city of Totoras, province of Santa Fe, Argentina, during the period 1990-2009. The evidence confirm previous results showing that greater individual production at the end of the productive life of cows do not always guarantee a better result in terms of productive efficiency. The milk index, as an indicator of productive efficiency, allows a better assessment of the performance of dairy cows kept on pasture systems. It is concluded that this indicator has intrinsic advantages as it quantifies the level of adjustment between the genetic potential of the herd for milk production and the particular characteristics of the production system in which that potential is expressed. Key words: milk index, genotype x environment interaction, artificial selection, imported semen